Toxicity Assessment and in vivo Anticancer Efficacy of Artemisinin–aspirin Co-loaded Liposomes - Thi Thanh, Huong Ha; Le Quang, Huan; Thi Ngan, Dang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
This study focuses on the development of an artemisinin–aspirin co-loaded liposome system aimed at enhancing anticancer efficacy while minimizing systemic toxicity. The liposomes were prepared using the thin-film hydration method combined with ultrasonication, resulting in an average particle size of 120–150 nm, with a narrow size distribution and high stability during storage. Acute and subacute toxicity tests in albino mice demonstrated that the formulation is safe, showing no adverse effects on behavior, liver or kidney functions, or fundamental physiological indices. In experimental cancer models, tumor volume decreased by 10–20% compared to the control group after 15–20 days of treatment. Following 25 days, the reduction reached 70–90%, with some subjects showing near-complete tumor regression. The mechanism of action is hypothesized to involve iron-dependent cell death (ferroptosis), inhibition of angiogenesis, and modulation of inflammatory responses, collectively suppressing tumor growth and metastasis. These preclinical results suggest that artemisinin–aspirin co-loaded liposomes hold significant potential as a novel drug delivery system to enhance the effectiveness of cancer therapies.